Francois Jacobus van Zyl, hoogleraar 1960-1978 - Merwe, P. J. van der (Hervormde teologiese studies, 1992)
Francois Jacobus van Zyl, professor 1960-1978 Professor Francois Jacobus van Zyl (6th May 1913-) served as head of the Department of Science of Religion and Missiology, Faculty of Theology (Sec A), University of Pretoria, during the period 1960-1978. This article (compiled from two previously published articles) contains a short biography, a discussion of his views on theology, Science of Religion, Philosophy of Religion, and Missiology. He is portrayed as a theologian with Barthian convictions. He worked from a broad theological base which can be described as ‘theology of the Word’. His primary audience was the Nederduitsch Hervormde Kerk and his theological activities (especially in the period 1960-1983) must be seen in relation to his influential role in the same church.